Company Profile Printing As A Media To Support Promotion And Information For Digital Printing Resolution Companies - Yudha Ardianto; Edy Jogatama Purhita (International Journal of Graphic Design, 2023)
Digital printing resolution using promotional media and information there are still obstacles, where promotional activities and information use round tags and only from word of mouth, this causes promotional and information media using business cards to have limitations in conveying information and word of mouth is felt to be outdated. era. Writer interested stage study To use help in increase media quality promotions and company information . Development model used​ that is research and development (Research and Development / R&D) and in development software application use Language programming Corel Draw and Adobe Photoshop. The research results obtained form company profile book Which can be used as a promotional and information media compete in this era now and can deliver sufficient information​ as Power attract candidates​ consumer . Based on the results of a questionnaire conducted on 30 respondents, the information aspect received a score of 447 , namely enter in category “ very agree ”, on aspects promotion get score 334 ie enter in category “ very agree ”, on aspects design get score 323 ie enter in category “ very agree ”, so the research results show “ very agree ” printed company profile created researcher Can used as promotional and information media on digital printing resolution .